A Comparison of a Behavioural and a Cognitive-Behavioural Approach to the Management of Chronic Tic Disorders - O'Connor, K.; Gareau, D.; Borgeat, F. (Clinical psychology and psychotherapy, 1997)
Two related studies explored the contribution of cognitive interventions to aiding ‘habit reversal’ treatment in chronic tic disorders. In the first study, two groups of chronic tic disordered subjects received either a standard behavioural intervention, modelled on Azrin and Nunn's (1973) ‘habit reversal’ technique (n = 7) or, a cognitive‐oriented treatment aimed at modifying anticipations in high risk tic situations (n = 7). The two groups were matched pre‐treatment, and clinically assessed post treatment, and at 3‐month and 2‐year follow‐up. There were no significant differences in clinical outcome, and both groups showed lower EMG level, and reported reduced tic frequency, and an increased degree of control over the tic. In a second series of case studies, the cognitive approach was extended to modify not only anticipations in high risk situations, but also the tic clients' overactive style of planning action. The cognitive model views perfectionist expectations about personal organization as a source of the frustration, and tension, which can provoke tics. In conclusion, although a cognitive approach may not be necessary to reduce tic frequency, it can facilitate tic management. © 1997 John Wiley & Sons, Ltd.